ANALISIS PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DENGAN MENGGUNAKAN KURIKULUM 2013 DI SMA NEGERI 1 LINTAU BUO KABUPATEN TANAH DATAR - Syafrizal Syafrizal (IAIN Batusangkar, 2016)
The purpose of this study was to describe the learning process, and obstacles encountered the learning of Islamic Education and Character by using Curriculum 2013 in State High School 1 Lintau Buo. The type of the research is descriptive by using Mix Method. The informants in this research were teachers of Islamic Education and Character, students and headmaster. The data collection techniquee were used in this study interview, observation and documentation. The results obtained indicate that the learning process of Islamic Education and Character has been implemented. However, there were some components of the learning process that has not been done as it should be such using the scientific approach, the use of the media, the use of teaching materials and handling students’ character. The efforts were done by school in implementing the curriculum 2013 were providing and expanding school’s facilities, conduct training, supervision and evaluation of teachers and students.Keywords: Islamic Education and Character, Learning Process, Curriculum 2013, State High School 1 Lintau Buo